The Rise and Fall of Adam and Eve: the Story That Created Us - Greenblatt, Stephen (W. W. Norton & Company, Incorporated, 2017)
"Endlessly illuminating and a sheer pleasure to read." --Jack Miles, author of God: A Biography Daring to take the great biblical account of human origins seriously, but without credulity.